Identifikasi Parasit Pentastomida pada Biawak Air (Varanus salvator) yang akan dikonsumsi - Andhika Yudhantama Subroto; I Komang Wiarsa Sardjana; Moh Sukmanadi; E Djoko Poetranto; Kusnoto Kusnoto; Agus Sunarso (Journal of Parasite Science (JoPS), 2020)
This study aims to determine the pentastomide parasite that infects the digestive tract of giant water lizards examined in Laboratory of Parasitology Department, Faculty of Veterinary Medicine, Airlangga University. In this study, three sample were found to be infected with pentastomide parasite in the lung. The phase found was adult phase pentastomide; it has pentastomide spermatheca which shows that this parasite is female.